STRUCTURE AND DYNAMICS OF THE ECONOMY IN BANDUNG CITY - Kharisma, Bayu; Remi, Sutyastie S. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study analyzes the structure and dynamics of the economy by examining the potential of economic sectors and identifying the leading sectors in Bandung City from 2010 to 2023. The methods used are LQ analysis, MRP, Overlay, Shift-Share, and Klassen Typology. The results of the study indicate a strong dominance of the tertiary sector as the central pillar, with 13 out of 17 sectors identified as base and prospective sectors. The Information and Communication, Health Services and Social Activities, Business Services, and Other Services sectors demonstrate competitive advantages and high contributions, making them priorities for development. Although positive growth is supported by competitive advantages (141.35 percent), the negative industrial mix (-113.08 percent) suggests potential for a structural slowdown. The Agriculture and Manufacturing sectors are relatively underdeveloped. Meanwhile, the results of the class typology indicate that various sectors in the city of Bandung fall into the categories of advanced and rapidly growing sectors, rapidly developing sectors, advanced but constrained sectors, and relatively lagging sectors, based on the economic growth conditions of each sector. Development in leading and promising sectors must be prioritized, along with innovative strategies for lagging sectors to achieve inclusive and sustainable economic growth.